2017
DOI: 10.1016/j.jplph.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of leaf somatic embryogenesis involves high pectin esterification, auxin accumulation and DNA demethylation in Quercus alba

Abstract: Somatic embryogenesis is considered a convenient tool for investigating the regulating mechanisms of embryo formation; it is also a feasible system for in vitro regeneration procedures, with many advantages in woody species. Nevertheless, trees have shown recalcitrance to somatic embryogenesis, and its efficiency remains very low in many cases. Consequently, despite the clear potential of somatic embryogenesis in tree breeding programs, its application is limited since factors responsible for embryogenesis ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 76 publications
4
36
0
Order By: Relevance
“…characterized by large nuclei and homogenous euchromatin (Grafi et al, 2011). During microspore embryogenesis, changes in global DNA methylation levels have been observed in various herbaceous and woody species (Corredoira et al, 2017;El-Tantawy et al, 2014;Rodriguez-Sanz et al, 2014b;Solis et al, 2012;De-la-Peña et al, 2015;. Using quantitative biochemical assays and immunolocalization of 5deoxy-methyl-cytosine (5mdC), these studies demonstrated that microspore reprogramming and embryogenesis initiation involve a global DNA hypomethylation.…”
Section: Several Reports Have Related Totipotency Of Cells To An Openmentioning
confidence: 99%
“…characterized by large nuclei and homogenous euchromatin (Grafi et al, 2011). During microspore embryogenesis, changes in global DNA methylation levels have been observed in various herbaceous and woody species (Corredoira et al, 2017;El-Tantawy et al, 2014;Rodriguez-Sanz et al, 2014b;Solis et al, 2012;De-la-Peña et al, 2015;. Using quantitative biochemical assays and immunolocalization of 5deoxy-methyl-cytosine (5mdC), these studies demonstrated that microspore reprogramming and embryogenesis initiation involve a global DNA hypomethylation.…”
Section: Several Reports Have Related Totipotency Of Cells To An Openmentioning
confidence: 99%
“…Previous studies have shown modifications in global DNA methylation that accompanied the change in developmental program of the microspore toward embryogenesis, in very different plant species, like Brassica napus , Hordeum vulgare , Quercus suber and Q. alba (Solis et al, 2012; Testillano et al, 2013; El-Tantawy et al, 2014; Rodriguez-Sanz et al, 2014a; Corredoira et al, 2017), indicating an epigenetic reprogramming after microspore induction to a totipotent state and embryogenesis initiation. More recently, it has been demonstrated that treatment with the DNA demethylating agent azacytidine reduces global DNA methylation of isolated microspore cultures and concomitantly increases embryogenesis initiation rates (Solis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, selection of suitable explants is a significant step for successful obtaining of somatic embryos and high frequency of plant regeneration achievement . Mainly, for this purpose scientists utilize histology methods that are time consuming and relatively expensive . Therefore, it is important to evolve the fluorescent dyes for fast diagnostics of somatic embryos obtained in in vitro conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there is a necessity for simple, fast and relatively inexpensive procedure to test the suitability of high regeneration method in early stage of callus cultivation. Mainly, histology methods that are time consuming and relatively expensive are utilized for this purpose . In previous studies, potential‐sensitive fluorescent dyes were used to visualize plant mitochondria and nuclei, cell‐to‐cell transport trough plasmodesmata and pigment metabolic pathways .…”
Section: Introductionmentioning
confidence: 99%